Managing Public Information Governance in Indonesia: A SMART Transparency Approach Based on Information Technology and Artificial Intelligence - Abdul Ghofar; Afrizal Hendra; Tuty Sariwulan; Antoni Ludfi Arifin (Dinasti International Journal of Education Management and Social Science, 2026)
Public information disclosure constitutes a fundamental prerequisite for democratic, transparent, and accountable governance. Although Law Number 14 of 2008 concerning Public Information Disclosure provides a strong legal foundation, existing transparency practices in Indonesia remain predominantly administrative and insufficiently integrated with organisational performance governance. Previous studies have largely focused on regulatory compliance and implementation mechanisms, while limited attention has been given to positioning transparency as a data-driven governance system supported by digital technology. Responding to this gap, this study examines the relevance and implementation strategies of SMART Transparency based on the principles of Specific, Measurable, Accessible, Relevant, and Timely as an integrative model of public information governance supported by information technology and artificial intelligence (AI). This research employs a qualitative literature review analysing regulatory frameworks, institutional reports, and national and international scholarly publications published between 2015 and 2025 using thematic analysis. The findings demonstrate that SMART Transparency enables the transformation of public information disclosure from procedural openness into performance-based governance through digital service integration, AI-assisted monitoring and dispute resolution, and strengthened public literacy and electoral oversight. Theoretically, this study contributes by reconceptualising transparency as a measurable governance framework integrating accountability, digital governance, and adaptive public management in the digital era.